2013
DOI: 10.1103/physrevb.87.075207
|View full text |Cite
|
Sign up to set email alerts
|

Formation energies of group I and II metal oxides using random phase approximation

Abstract: The enthalpy of formation for 23 metal oxides, which include group I and II as well as two transition metals (Ti and Ru), are calculated using random phase approximation (RPA). Compared to PBE xc-functional, RPA reduces the mean absolute error (MAE) per oxygen from 0.44 eV to 0.15 eV. The calculated deviations with experiments are seperated into two parts: a systematic and uniform error related to the reference energy of O and the ones specific to diffferent oxidation statesOur results show that RPA improves b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 36 publications
1
39
2
Order By: Relevance
“…[28], which reported convergence within 50 meV for RPA oxide formation energies. References [21,22] showed that rAPBE converges as fast or faster than RPA with respect to k points.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…[28], which reported convergence within 50 meV for RPA oxide formation energies. References [21,22] showed that rAPBE converges as fast or faster than RPA with respect to k points.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Apart from their general importance, this set of oxides was recently examined using the RPA [28] and experimental formation enthalpies are available making it an ideal case for benchmarking of the renormalized kernels.…”
Section: B the Oxidesmentioning
confidence: 99%
“…Specifically, the RPA correlation energy should capture long-range dispersive interactions that are missing in the Hubbard-U corrections [12,13]. Recent work has demonstrated the good performance of the RPA + EXX approach for calculating the formation energies and relative stabilities of transition metal oxides [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…(1) gives a simple framework for calculating correlation energies in terms of the excited states of a noninteracting auxiliary system and is expected to provide a high degree of accuracy with simple approximations for the xc kernel. In particular, if we use f xc ¼ 0 we obtain the random phase approximation (RPA) [4], which has been shown to give an accurate account of dispersive interactions, static correlation, and weak covalent bonds, and is presently considered state of the art in ab initio electronic structure theory involving solid state systems [5][6][7][8][9][10][11][12][13]. Nevertheless, the RPA suffers from large selfcorrelation errors and predicts too weak binding of solids and molecules, which have severely limited the universal applicability of the method.…”
mentioning
confidence: 99%